Test and effect analysis of hydraulic automatic pressure regulating water injection device in Shengli Oilfield. (7th May 2020) - Cui, Yuhai; Feng, Jiehua; Zhao, Dongya
In the later stage of oilfield exploitation, due to the decrease of fossil oil, the oil recovery from the oilfield will be reduced; even the production can be stopped. In order to stabilise the production of the oilfield, it is an effective measure to develop the oilfield by water injection. Therefore, it is very important to study the pressure regulating water injection technology, and the hydraulic automatic regulating device is the key. In this paper, a set of hydraulic automatic pressure regulating water injection devices is developed, which mainly includes three parts: screw motor module, screw pump module, and transmission device between screw motor output shaft and screw pump input shaft. The shunt injection of each layer can be realised without deployment by the automatic pressure regulating device. The change of total water injection volume can automatically adapt to the reservoirs according to the flow distribution ratio. At the same time, the test and field experiment in Shengli Oilfield, Dongying, China, show that the developed device has good energy saving effects.